Польский идиолект польcко-литовского пограничья (из Суженской апилинки Вильнюсского рaйoна) - Коницкая, Елена Михайловна (Kalbotyra, 1997)
The article examines phonetic and mоrpholоgiс particularities of Polish idialect from Polish patois circulating in the Northern part of Vilnius region of Lithuania in the domain belonging to Lithuania within the period between World War I and World War II. The detected phenomenon is compared with those phenomena, verified in different researches of Polish patois, specially in the works of Н. Turska. There were identified some slight idialect distinctions, influenced by Lithuania language and the tendency towards accuracy of Polish discourse. In spite of there distinctions, under bilingual condition and without supporting influence of Roman-Catholic church and Polish school, high level of integrity of Polish language is verified. This points to very deep roots of such а phenomеnon as Polish language of Lithuania.